Composting kinetics for mixture of poultry manure and wheat straw based on volatile solids content - Karić, Ervin; Petrić, Ivan; Mustafić, Nesib (Journal of Engineering & Processing Management, 2017)
The aim of this study was to determine the composting kinetics for mixture of poultry manure and wheat straw based on the volatile solids content. Experimental data was fitted with the first-order and the nth-order kinetic model. The nth-order kinetic model showed better prediction performance than the firstorder kinetic model. For the first-order kinetic model, maximum and mean differences between experimental and simulation results for the content of volatile solids were 5.43% and 3.00%, for the first reactor, and 4.68% and 2.12% for the second reactor, respectively, for the nth-order kinetic model, maximum and mean differences were 4.92% and 1.68%, for the first reactor, and 4.09% and 1.42% for the second reactor, respectively.